ALFABETIZACIÓN EMOCIONAL EN CONTEXTOS VULNERABLES CON DIBUJOS DIGITALES - HOLGUIN-ALVAREZ, JHON (2022)
The objective sought to determine the effects on emotional literacy in the elaboration of digital drawings and traditional drawings in the cooperative and individual pedagogical format. 120 schoolchildren from vulnerable contexts participated. The data was collected by a scale based on Fury's proposals. Se advierten efectos de mejora en el cambio de laalfabetización emocional, y en sus componentes de expresividad y valencia. Improvement effects are noted in the change of emotionalliteracy, and in its components of expressiveness and valence. A higherlevel was detected in the change from negative to positive emotions in thedrawings of children who used tablets collaboratively, as opposed to thosewho did so individually.